The Degree to Which Intermediate First-Graders in Jamoum Governorate Saudi Arabia Have Basic Skills in Mathematics - Al-Maliki, AbdulMalik Misfer; Al-Sulami, Othman Abdullah (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the degree to which first-grade students possess an average of some basic skills in mathematics in Jamoum Governorate. The study population was represented in all first-grade intermediate students in Al-Jamoum Governorate, Kingdom of Saudi Arabia for the third semester of the academic year 1443 AH / 2022 AD, including (792) students, belonging to (15) schools, (112) students were selected as a sample for the study in a random way, and the researchers used the experimental method, and the study tool was an achievement test for mathematics for the first intermediate grade for the third semester prepared by the researchers to identify the degree to which first-grade students possess an average of basic skills in mathematics. The study reached many results, the most important of which are the following: skill (evaluation) ranked first with an arithmetic average (4.29) and a percentage of (86%), skill (understanding) came in second place with an arithmetic average (4.13) and a percentage of (83%). Skill (knowledge) came in third place with an arithmetic average (3.97) and a percentage of (79%). The study recommended updating the vocabulary of the curriculum for mathematics, especially in the curricula of the basic and intermediate stage, keeping pace with the modernization of teaching aids, and continuous follow-up of students through surprise exams. The study suggested conducting more qualitative studies to address different grades and stages of study to identify the reality of educational practices for mathematics.
Keywords: Basic Skills; Mathematical Skills